Challenges in the diagnosis and treatment of neurosarcoidosis. (3rd October 2015) - Tana, Claudio; Wegener, Susanne; Borys, Ewa; Pambuccian, Stefan; Tchernev, Georgi; Tana, Marco; Adele Giamberardino, Maria; Silingardi, Mauro
Abstract: The diagnosis and treatment of neurosarcoidosis can be very challenging for several reasons. It affects clinically 5%–10% of sarcoidosis patients, but can be found in up to 25% of autopsies. These data reveal that a high percentage of asymptomatic or misdiagnosed cases can be missed at an initial diagnostic approach. Clinical and imaging findings are often non-specific since they can be found in a large number of neurological disorders. Histopathology can also be confounding if not performed by an expert pathologist and not placed in an appropriate clinical context. In this review, we discuss clinical features, laboratory findings, imaging, and histology of neurosarcoidosis, and we report current evidence regarding drug therapy. We conclude that a correct diagnostic approach should include a multidisciplinary evaluation involving clinicians, radiologists, and pathologists and that future studies should evaluate the genetic signature of neurosarcoidosis as they could be helpful in the assessment of this uncommon disease. With head-to-head comparisons of medical treatment for neurosarcoidosis still lacking due to the rarity of the disease and an increasing number of immunomodulating therapies at hand, novel therapeutic approaches are to be expected within the next few years. Key Messages: Neurosarcoidosis is a rare disorder that affects clinically 5%–10% of sarcoidosis patients, but can be found in up to 25% of autopsies, revealing that a high percentage of asymptomatic or misdiagnosed cases can be missed at an initial diagnostic approach. A multidisciplinary evaluation is useful to achieve a correct diagnosis because clinical and imaging findings are often non-specific. Corticosteroids are the first-line treatment for neurosarcoidosis, followed by steroid-sparing immune-modulating agents if prednisone therapy is insufficient.